اعادة الهندسة الاداریة کمدخل لتمیز مؤسسات المعرفة - د. أمنیة خیر توفیق (المجلة الدولية لعلوم المكتبات والمعلومات)
The study sought to explore the importance of applying the re-engineeringapproach to knowledge institutions in order to institutionalize modern methods inmanaging knowledge institutions because they have important and vital additionsto the strategic policies of knowledge institutions.It also informs employees of knowledge institutions about re-engineering ,on the move towards adoption of modern management methods , and changethe working procedures of the institutions of knowledge for the better , It is basedon the descriptive approach , as it is best suited to identify : concepts andframeworks of knowledge of the method of re-engineering , types ofadministrative re-engineering required by the knowledge institutions , and toclarify the importance of the application of the approach of re-engineering ofknowledge institutions , the consequences of its application , and to find ways tomeet the challenges that may impede this application in knowledge institutions ,The most important results of the study are : The introduction of administrativereengineering allows for radical improvements , not limited to partial modificationsof all components of the knowledge institution . Different types of knowledgeinstitutions need to re-engineer management , whether they suffer or not fromproblems of re-engineering in knowledge institutions : Service of reengineering ,reengineering process , reengineering ofmanagement systems , reengineering requires management improvementand development especially in the areas of organizational work , process outputs, system , and resources .A set of reengineering approaches that can be reliably applied toknowledge institutions is available from the results of the application of thereengineering approach to knowledge institutions : the transformation ofbusiness units from functional departments to operations teams , transformingjobs from simple tasks to complex work , the focus shifts on performancestandards , rewards and activities to results , Examples of obstacles that arepreventing the re-engineering approach to knowledge. institutions : the existenceof a culture of resistance to change, the lack of clarity of the knowledge        institution's vision , its organizational culture in the process of re-engineering, theuse of non-cadres to lead the process of administrative re-engineering, assigningadministrative re-engineering to retiring individuals , non-discrimination betweenadministrative re-engineering and other change programs, An example of therequirements for : The adequate awareness of the wishes of the beneficiaries ,an analysis of the institution's position and the design of the objectives of change, the belief of the senior management in the importance of change andencouragement of employees and understanding of the process of reengineeringadministrative management .Recommendations of the study : The need to adopt conscious leaders indifferent types of knowledge institutions , providing the necessary budget forapplying administrative reengineering in knowledge institutions , establishing aspecialized unit for reengineering of knowledge institutions , setting a plan for aspecific period of time of different types , especially the leaders in which newskills and knowledge on the reengineering management , monitoring theexperiences and management practices distinct in the field of reengineeringmanagement services facilities to document and benefit from them , increasingdependence needed to support administrative processes of reengineeringmethod of information technology .